Digital Hospitals. How to navigate them? - Książek, Piotr; Drop, Bartłomiej; Furtak, Marzena; Warchoł-Sławińska, Ewa (Polish Journal of Public Health, 2011)
The purpose of this work is to explain and discuss the benefits of introducing new IT systems to hospitals, especially for diagnostic laboratories, hospital wards, hospital pharmacies, as well as to demonstrate the advantages of systems in operation and running of a health care facility. This article is a review of the basic concepts related to the much needed computer technology in hospitals nowadays; it explains and describes the basic functioning of information systems – their individual modules within the entire health care units. The beginning of the text presents a historical outline of the formation and implementation of various digital systems in health institutions in the world, as well as in Poland. The text also outlines the problems, aims to achieve appropriate solutions, and demonstrates the advantages and implementation of IT in healthcare facility operation. The text also describes the Polish medical market and the dilemmas of health care issues affecting this sector at the time when the hospital directors/managers make decision to introduce new technology to their hospitals. This article also responds to various questions, for example why and how to computerize the facility. It briefly describes the operations of individual modules installed in the hospital, from the hospital system HIS, radiological RIS, archiving PACS, through the laboratory system LIS, ending with the pharmaceutical PIS. The conclusion of this work shows the benefits and effects of the implementation of mobile medical informatics. The text allows to find answers why the system implementation and application of modern computer technology in the hospital is so important throughout the treatment process. It explains that due to this operation the hospital staff have access to all medical data of their patients, it becomes also possible to send information between health care units throughout the country and even the world, where the computer with the appropriately installed software has become an indispensable tool for collecting and processing information.